Exploring the differential impact of a male celebrity endorser on brand trust in Scarlett Cosmetics across genders - Abdul Gofur; Hanuna Shafariah (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
This study aims to analyze the influence of celebrity endorsers on brand trust, considering gender as a moderating variable, with a focus on the use of celebrity endorsements for cosmetic products in Indonesia. Based on the Source Credibility Theory, this study employs a quantitative method using Moderated Regression Analysis (MRA) with 115 respondents in Jakarta, who were obtained through a chain referral system technique. The results show that celebrity endorsers significantly increase brand trust, in line with previous findings that support the credibility of endorsers. A crucial finding is the role of gender as a significant moderator, where the influence of celebrity endorsers is more substantial on male consumers than female consumers in the context of women's cosmetic products. Managerial implications suggest that marketers consider gender dynamics in the selection of celebrity endorsers to optimize marketing strategies and campaign effectiveness, even for products traditionally aimed at a particular gender. This study contributes to enriching the marketing literature by providing empirical insights from the Indonesian context regarding the role of gender in moderating the influence of celebrity endorsers.